Occurrence, risk assessment and public risk perception of multiclass endocrine disrupting compounds in drinking water supply system - Wee, Sze Yee (2019)
Presence of endocrine disrupting compounds (EDCs) in drinking water concerns the security and sustainability of the supply system. The problem is not only limited to the pollution level of EDCs in raw and treated water, but also exposure of organisms to EDCs especially human via daily drinking water consumption. The trace level in tap water challenges the identification of the multiclass EDCs. With the wide ranging nature and characteristics of the pollutants themselves (if known at all), the analytical methods were made available only to single EDC group and/or its metabolites. The limited EDC monitoring in tap water and evidence of human exposure risk caused the increase of associated risks as they may have been underestimated and even unknown. The present study describes an analytical method based on solid phase extraction followed by liquid chromatography-tandem mass spectrometry (SPE-LC-MS/MS) for analysis of multiclass EDCs (hormones, pharmaceuticals, plasticizers and pesticides) in tap water in a single extraction step. The method was validated with recovery between 85 to 119% for most of the EDCs and method detection limit ranging from 0.01 to 2.56 ng/L. Method precision was achieved with linearity > 0.9 and relative standard deviation less than 15% for the targeted compounds. A total of 14 EDCs i.e., five hormones, seven pharmaceuticals, one plasticizer and one pesticide was detected in Langat River, a drinking water source treated for Malaysian drinking water supply. Chloramphenicol and 4-nonylphenol were below method detection limit in both raw and treated water. Prevalent occurrence of EDCs was observed in Malaysian tap water up to 66.40 ng/L (bisphenol A). Triclosan and 4-octylphenol were only detected in tap water at concentration up to 9.74 and 0.44 ng/L, respectively. Variation also observed in different housing types. For local exposure, human health risk assessment was based on human morphological, drinking water consumption patterns and household practices collected through a survey using a newly developed and verified questionnaire. This study captured the complex dynamic of the public-perceived risks on safe drinking water quality in regards to EDCs and the influencing factors, providing a comprehensive conceptualization of the predictors of environmental risk perception, trust, attitude and knowledge. The public tend to perceive the risks through nonrational processing system that highly subjected to cognitive and affective influences. Also, the perceived EDCs contamination in tap water was found to have no association with measured values. Monitoring and risk assessment are the initial processes in multibarrier approach in drinking water supply system for safe water resources. Fulfilling the gap of risk perception and identification of the role of risk perception through development of risk perception model were useful in formulating the efficient preventive and intervention measures with known target groups and materials. Higher trust towards stakeholders and perceived risk on human exposure to environmental risk, as well as positive attitude towards drinking water quality improvements can increase the public perceived risk on drinking water. The subsequent public improvement in terms of risk behavior development was also essential for effective risk governance and communication, supporting the aforementioned multibarrier approach.